An Empiric Experience Implementing a Methodology to Improve the Entrepreneurial Support System: Creating Social Value Through Collaboration and Co-creation - Cearra, Jokin; Saiz-Santos, María; Barrutia, Jon (Frontiers in Psychology, 2021)
Entrepreneurship and entrepreneurial people are considered one of the sources of innovation and agents of change in the developed societies. Entrepreneurial ecosystems are the environment in which such phenomena occurs. A common problem in many of them is caused by the atomization of the system of agencies and organisms supporting the entrepreneurial activity. A social experiment is designed with the objective of testing the value of a solution based on a technological platform to solve that governance problem. The methodology is based on a dynamic scheme seeking the involvement and collaboration of all the stakeholders and goes through a co-creative process inspired by design thinking. The theoretical framework includes the entrepreneurial ecosystem literature and the governance theory and takes into account the need to involve all the stakeholders in order to improve the previous situation and favoring the achievement of the Sustainable Development Goals. As it is a real experience, a social network supported by an ICT based platform is formally created, contributing to alleviate the atomization problem and generating social value at the same time. This experience carried out in the Spanish province of Biscay at the Basque Country might be a pilot test in order to extend the solution to other entrepreneurial ecosystems with similar casuistic.